Away in a manger a story of the Nativity - Nussbaumer, Mares; Nussbaumer, Paul. (New York Harcourt, Brace & World, 1965)
Retells the story of the birth of Jesus with a Swiss setting.
Translation of Ihr Kinderlein kommet.
Keywords: Jesus Christ -- Nativity -- Juvenile literature; Jesus Christ -- Nativity; Bible stories -- N.T.